Geometric Thinking Ability Based on Van Hiele’s Theory in Ethnomathematics-Based Conicongruence Learning at Museum Benteng Vredeburg - Iskandar, Iskandar; Marsigit, Marsigit (Proceeding International Conference on Religion, Science and Education, 2026)
This study aims to determine the effectiveness of learning and analyse the improvement of geometric thinking levels according to Van Hiele’s theory. As well as how students’ experience of learning ethnomathematics-based congruence at Museum Benteng Vredeburg. The ethnomathematics approach is used to integrate local cultural concepts into mathematics learning, in order to improve students’ geometric thinking skills. This study used quantitative and qualitative approaches involving junior high school students as research subjects. Data were collected through geometry thinking ability tests, interviews, and observations during the learning process. Analysis was conducted to identify students’ geometry thinking level according to the five stages in Van Hiele’s Theory, namely visualisation, analysis, informal deduction, deduction, and rigor. The results showed that the ethnomathematics-based learning approach was effectively implemented and was able to facilitate students in reaching higher stages of geometry thinking. The use of cultural elements, such as the building structure in Museum Benteng Vredeburg, provides a relevant concrete context and increases the level of geometry thinking. This research contributes to the development of culture-based mathematics learning design, especially to improve students’ geometry thinking skills.